The borax efficacy in the treatment of aphthous stomatitis - Yolanda Iglesias Sanches; Julia Moya Martínez; Semiramis Garcia Gómez; Norelis García Lezcano (Medisur)
Background: aphthous stomatitis is a chronic disease characterized by the non-keratinized oral mucosa ulceration, which presents acutely and painfully. Objective: to evaluate the efficacy of borax in the aphthous stomatitis treatment. Methods: an analytical, longitudinal prospective study was carried out in the North Polyclinic Stomatology Department, Ángel del Castillo Agramonte, in the Florida municipality, from December 2019 to April 2021. 139 patients were studied and the sample was made up of 70 patients selected by a simple random method. It was divided into two groups: a study group and a control group to which a homeopathic treatment with borax and a conventional treatment were applied, respectively. Results: the most affected age range was 21-30 years old, and the female sex was the most represented; the lips were the most affected site and aphthous stomatitis prevailed in its minor form. At each control visit, a better evolution of pain, burning, and healing of the lesions was observed with the homeopathic treatment than with the conventional one; an effectiveness of 100% was observed in the patients treated with borax and the majority of the patients were satisfied with the homeopathic treatment received. Conclusions: borax is effective for the treatment of aphthous stomatitis.